1999
DOI: 10.1021/cm981145w
|View full text |Cite
|
Sign up to set email alerts
|

Improved Oxide Ion Conductivity in La0.8Sr0.2Ga0.8Mg0.2O3 by Doping Co

Abstract: The effects of doping Co for the Ga site on the oxide ion conductivity of La 0.8 Sr 0.2 Ga 0.8 -Mg 0.2 O 3 have been investigated in detail. It was found that doping Co is effective for enhancing the oxide ion conductivity. In particular, a significant increase in conductivity in the low-temperature range was observed. The electrical conductivity was monotonically increased; however, the transport number for the oxide ion decreased with an increasing amount of Co. Considering the transport number and ion trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
93
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 23 publications
4
93
0
1
Order By: Relevance
“…4 Following the initial discovery, [1][2][3][4][5] numerous experimental studies have been carried out on LSGM materials, which also include the effect of transition-metal doping. [6][7][8][9][10][11] It is generally believed that doping with a transition metal cation is undesirable for the ionic conductor due to the appearance of n-or p-type conduction. However, it was found that the oxide ion conductivity was also improved by doping Co for Ga in LaGaO 3 -based perovskites, 7 although hole conduction was detected at high oxygen partial pressures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Following the initial discovery, [1][2][3][4][5] numerous experimental studies have been carried out on LSGM materials, which also include the effect of transition-metal doping. [6][7][8][9][10][11] It is generally believed that doping with a transition metal cation is undesirable for the ionic conductor due to the appearance of n-or p-type conduction. However, it was found that the oxide ion conductivity was also improved by doping Co for Ga in LaGaO 3 -based perovskites, 7 although hole conduction was detected at high oxygen partial pressures.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was found that the oxide ion conductivity was also improved by doping Co for Ga in LaGaO 3 -based perovskites, 7 although hole conduction was detected at high oxygen partial pressures. 7,11 Nevertheless, Yamada et al 12 demonstrated that the Co-doped LSGM (LSGMC) can be used as an electrolyte for SOFCs operating at 770 • C. The 1-kW stack they tested had a fuel electrode that consisted of a mixture of NiO and Ce 0.8 Sm 0.2 O 2−δ (SDC) and a Sm 0.5 Sr 0.5 CoO 3−δ (SSC) cathode.…”
Section: Introductionmentioning
confidence: 99%
“…2), 3) In 1995, Nakayama et al reported that the apatite-type Ln-Si-O rare earth silicates exhibited a very high oxide ionic conductivity. 4), 5) The O 2-ions at the 2a sites of the channel along the c-acis in the apatite-type (P63/m) structure are the mobile species producing the high conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Fe, Mn, Sc, etc.) are predicted to substitute preferentially for Ga 3+ position (4), hence the influence of different B-site substitutions on the transport and physicochemical properties of lanthanum gallate has been studied in order to develop novel materials for electrochemical applications (5,6). However, a negligible electronic conductivity is required for many applications, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ishihara et al (5) reported that the introduction of small amounts of cobalt into the gallium sites may result in an increase of the ionic conductivity in LSGM material. Nevertheless, it was also found that the electronic conductivity increased and consequently, the ionic transport number decreased with the increasing of cobalt content.…”
Section: Introductionmentioning
confidence: 99%